Approaches to Indonesia's Foreign Policy: Area Studies, FPA Theory, and Global IR - I Gede Wahyu Wicaksana; Moch Faisal Karim (JAS (Journal of ASEAN Studies), 2022)
This article traces the evolution of Indonesia's foreign policy studies, highlighting the major theoretical and methodological trends that have shaped their current form. As a starting point, we introduce a discourse on non-Western Foreign Policy Analysis (FPA), having developed beyond the dominance of the Western-rooted International Relations (IR) discipline. The authors encounter that Indonesia's foreign policy studies evolve through two stages. The first stage occurred during the Cold War until the early 2000s. It demonstrated a scholarship development characterized by an attempt to promote a national-focused or area studies perspective, despite the influence of realism and positivism. The second stage, visible since the mid-2000s, shows the advancement of diverse theory-driven inquiries, having been moved by the younger generation of scholars more exposed to various theories and research methods in IR. Dealing with these two phases of the studies will likely build Indonesia's foreign policy studies' inclusive, critical, and unique identity. It can be realized by adopting and contextualizing approaches offered by state transformation theory, critical realism, and reflexive theorizing in IR to unpack the relatively overlooked aspects of Indonesia's foreign policy.